2023
DOI: 10.3390/nano13212860
|View full text |Cite
|
Sign up to set email alerts
|

Free Convection in a Square Ternary Hybrid Nanoliquid Chamber with Linearly Heating Adjacent Walls

Vemula Rajesh,
Mikhail Sheremet

Abstract: In this study, mathematical modeling of the energy transfer and flow characteristics of ternary nanoliquid in a square enclosure is performed. In the cavity considered, the left and bottom borders are warmed uniformly or non-uniformly when the rest of the borders are cooled. The robust finite element method with quads and triangles as elements is used to work out the control equations of the problem. The current study is validated against previously published works, and good agreement is shown. The isolines ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Table 2 details the physical characteristics of the ternary hybrid nanofluid, including its density (ρ thn f ), viscosity (µ thn f ), specific heat capacity ρc p thn f , volumetric thermal expansion coefficient ((ρβ) thn f ), and thermal conductivity (K thn f ). The correlation remains valid and yields accurate outcomes when the volume fraction of particles falls within the range of 0.01 to 0.1, and the temperature varies between 35 [38].…”
Section: Thermophysical Properties Of Ternary Hybrid Nanofluidmentioning
confidence: 83%
“…Table 2 details the physical characteristics of the ternary hybrid nanofluid, including its density (ρ thn f ), viscosity (µ thn f ), specific heat capacity ρc p thn f , volumetric thermal expansion coefficient ((ρβ) thn f ), and thermal conductivity (K thn f ). The correlation remains valid and yields accurate outcomes when the volume fraction of particles falls within the range of 0.01 to 0.1, and the temperature varies between 35 [38].…”
Section: Thermophysical Properties Of Ternary Hybrid Nanofluidmentioning
confidence: 83%
“…According to the results, the size of the internal object minimizes the space inside the wavy cavity, and it was found that D = 0.3 is the perfect size located within the center of the cavity. Rajesh and Sheremet [28] performed numerical simulations to investigate the phenomenon of free convection in a square cavity with a lid-driven flow. The cavity was filled with a ternary hybrid nanofluid, specifically composed of Cu-CuO-Al2O3 and water.…”
Section: Introductionmentioning
confidence: 99%